2018
DOI: 10.1111/1365-2664.13266
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between illegal hunting of ungulates, wild prey occurrence and livestock depredation rate by large carnivores

Abstract: 1. Illegal hunting of ungulates can reduce the prey base of carnivores, which can increase human-carnivore conflict (HCC) through livestock depredation. However, the relationship between ungulate poaching, wild prey abundance and livestock depredation has rarely been empirically studied.2. We surveyed 18 sites across the Hyrcanian forest in northern Iran; a global biodiversity hotspot under pressure from illegal hunting of ungulates, prey depletion, livestock grazing and HCC. We conducted three field surveys a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Density of wild herbivore prey is known to be a critical determinant of carnivore density (Carbone & Gittleman, 2002; Karanth et al., 2004; Suryawanshi et al., 2017). However, the role of wild herbivore density in determining the extent of livestock predation by carnivores is debatable (Bagchi & Mishra, 2006; Khorozyan et al., 2015; Meriggi et al., 1996; Meriggi & Lovari, 1996; Soofi et al., 2019; Suryawanshi et al., 2017). Studies investigating the impact of livestock abundance on predation levels have shown higher intensities of depredation in areas of higher livestock densities (Pimenta et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Density of wild herbivore prey is known to be a critical determinant of carnivore density (Carbone & Gittleman, 2002; Karanth et al., 2004; Suryawanshi et al., 2017). However, the role of wild herbivore density in determining the extent of livestock predation by carnivores is debatable (Bagchi & Mishra, 2006; Khorozyan et al., 2015; Meriggi et al., 1996; Meriggi & Lovari, 1996; Soofi et al., 2019; Suryawanshi et al., 2017). Studies investigating the impact of livestock abundance on predation levels have shown higher intensities of depredation in areas of higher livestock densities (Pimenta et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that where wolves are extirpated, ungulate numbers might rise dramatically, causing reduction of biological and morphological diversity in terrestrial and aquatic ecosystems (Ripple et al, 2014). On the other hand, where ungulate numbers and biodiversity are dramatically reduced by anthropogenic factors (e.g., poaching, habitat destruction and alteration, excessive farming and grazing by livestock) wolves can be a major cause of human-wildlife conflict (Tuğ, 2005; Soofi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As elsewhere, spatial data on poaching is unavailable in the Caucasus, preventing us from including poaching directly in our models. Yet poaching is a key threat to mountain ungulates in this region (Ghoddousi et al, 2019; Soofi et al, 2019; Zazanashvili & Mallon, 2009), as these species are preferred by poachers and easy to hunt (Ghoddousi et al, 2019), and because poaching is linked to transhumance grazing still found across large areas in the Caucasus (Gavashelishvili et al, 2018). Most extant bezoar goat populations we identified are confined to protected areas, even within otherwise larger patches of habitat (Figure 3, Figure S1, Supporting Information).…”
Section: Discussionmentioning
confidence: 99%